Peran Guru Dalam Pendidikan Karakter Anak Usia 5-6 Tahun - Ananda, Alma Muthia; Sjamsir, Hasbi; Pertiwi, Adharina Dian (Jurnal Ilmiah POTENSIA, 2025)
The purpose of this study is to outline the role that educators play as well as the challenges that children face when learning disciplinary character. A qualitative descriptive approach is the research methodology employed. Teachers and students in Group B1 provided the data sources for this study. In order to learn more about the role of teachers in the discipline character education of Group B1 students, data collection methods and tools were acquired through observations and interviews. Photographs and documents were utilized as supporting documentation in the study. Three triangulation techniques source triangulation, technique triangulation, and time triangulation were employed to assess the validity of the research data. The study's findings show that by using various instructional strategies that encourage active student participation, teachers can significantly contribute to the discipline development of their students. Teachers continue to work to establish a supportive learning environment that aids in the development of children's disciplinary character in spite of a number of obstacles. Thus, it is crucial that educational institutions give instructors the assistance they need to carry out this responsibility more successfully and to assist kids in forming moral character at a young age